Pertumbuhan Ekonomi dan Ketimpangan Wilayah di Kawasan Strategis SARBAGITA (Denpasar, Badung, Gianyar, Tabanan) - Putu Ayu Pramitha Purwanti; Ni Putu Wiwin Setyari (Jurnal Dinamika Ekonomi & Bisnis, 2021)
This study aims, firstly, to find out the category of district/city areas in the SARBAGITA area with Klassen typology. Second, knowing the level of economic inequality in urban districts in the SARBAGITA area with the Williamson index. Third, knowing the relationship between growth and economic inequality in the SARBAGITA region by testing the Kuznets hypothesis. The analysis was carried out using secondary data with the results, first, that in the SARBAGITA area there are still districts as relatively underdeveloped areas which indicate that the spread effect of the regional center development is not yet optimal. Second, the absolute level of economic inequality shows fluctuations, but if viewed based on trends, it shows a positive trend. This means that the longer the period, the higher the level of inequality. The final result is the proof of Kuznets hypothesis in the SARBAGITA area. At the beginning of the study period, economic growth was followed by an increase in inequality but at a certain point, the inequality decreased. Thus, we need a regional planning that can create a balance of economic growth so that inequality between regions can be minimized or even avoided.